Suicide attempts in bipolar I patients: impact of comorbid personality disorders - Bezerra, Severino (Braz J Psychiatry, 2017)
OBJECTIVE: To evaluate the association between personality disorders (PDs) and suicide attempts (SAs) in euthymic patients with type I bipolar disorder (BD). METHODS: One-hundred twenty patients with type I BD, with and without history of SA, were evaluated during euthymia. The assessment included a clinical and sociodemographic questionnaire, the Hamilton Depression Rating Scale, the Young Mania Rating Scale, the Barratt Impulsiveness Scale, and Structured Clinical Interviews for DSM-IV Axis I and II Disorders. Logistic regression was employed to determine associations between history of SA and patient characteristics. RESULTS: History of SA was significantly associated with comorbid axis I disorder, rapid cycling, high impulsivity (attentional, motor, non-planning, and total), having any PD, and cluster B and C PDs. Only cluster B PDs, high attentional impulsivity, and lack of paid occupation remained significant after multivariate analysis. CONCLUSIONS: Cluster B PDs were significantly associated with SA in patients with type I BD. High attentional impulsivity and lack of gainful employment were also associated with SA, which suggests that some cluster B clinical and social characteristics may exacerbate suicidal behavior in this population. This finding offers alternatives for new therapeutic interventions.